Recycling of Acetylcholine Receptors at Ectopic Postsynaptic Clusters Induced by Exogenous Agrin in Living Rats - Brenner, Hans Rudolf (2014)
During the development of the neuromuscular junction, motor axons induce the clustering of acetylcholine receptors (AChRs) and increase their metabolic stability in the muscle membrane. Here, we asked whether the synaptic organizer agrin might regulate the metabolic stability and density of AChRs by promoting the recycling of internalized AChRs, which would otherwise be destined for degradation, into synaptic sites. We show that at nerve-free AChR clusters induced by agrin in extrasynaptic membrane, internalized AChRs are driven back into the ectopic synaptic clusters where they intermingle with pre-existing and new receptors. The extent of AChR recycling depended on the strength of the agrin stimulus, but not on the development of junctional folds, another hallmark of mature postsynaptic membranes. In chronically denervated muscles, in which both AChR stability and recycling are significantly decreased by muscle inactivity, agrin maintained the amount of recycled AChRs at agrin-induced clusters at a level similar to that at denervated original endplates. In contrast, AChRs did not recycle at agrin-induced clusters in C2C12 or primary myotubes. Thus, in muscles in vivo, but not in cultured myotubes, neural agrin promotes the recycling of AChRs and thereby increases their metabolic stability.